Shape Your Eyes by Shutting Them - McCutcheon, Mark A. (Athabasca University Press, 2019)
In this inventive collection of poems, McCutcheon engages in sophisticated literary play and deploys the Surrealist practices of juxtaposition, cut-up, and defamiliarization. Moving from eroticism to the macabre and from transformative quotation to the individual idiom, Shape Your Eyes by Shutting Them explores intertextuality in poetry by challenging the cultural tradition of seeing quotation as derivative.